Propaganda antyżydowska w Generalnej Guberni, 1939–1945 - Grabowski, Jan (Zagłada Żydów. Studia i Materiały, 2010)
German propaganda in the General Government directed at the Poles was based on two permanent elements: on the one hand, it was about arousing aversion towards Soviet Russia and communism, and on the other hand, stirring anti-Semitic sentiments. Attempts at using anti-Allies propaganda at the beginning of the occupation turned out to be a failure. The only „distinct” slogans that found resonance in the Polish society were related to anti-communism and their aversion towards the Jews. Visual means were of special importance to German propagandists and they used them to exert influence on the Poles. Therefore, special emphasis was put on the distribution of posters and traveling exhibitions on anti-Semitism. Polish-language newsreels showed in theaters before the main feature were even more important. In all of these cases, Polish filmmakers, painters and graphic artists employed by thePropaganda Office played a prominent role.